Some reflections about the monetary policy of the government - Kh. Umarov; M. R. Obidova (Вестник Северо-Кавказского федерального университета)
Introduction. In modern conditions, issues of monetary circulation, proportionality and balance of the money market are the most important aspects of the financial stability of the national economy. The article emphasizes the importance of using factors to regulate monetary policy and the need to transform the state's monetary policy. The authors consider the views of economic schools regarding state monetary policy regimes. Attention is focused on the views of keynesian and monetarist doctrines on monetary policy.Goal. Analyze the state of the country’s money market, as well as analyze the problems of imbalances in the country’s money market, substantiate the contradictions between commodity and financial-value flows in the national economy, leading to a shortage of money. Prove the ineffectiveness of monetarist (neoliberal) recipes for the development of monetary circulation.Materials and conclusions. The study is based on the methods of dialectical, retrospective, descriptive, comparative analysis, absolute, average and relative values, as well as predictive analysis. A conclusion is made about considering the issues of applying effective monetary policy regimes.Results and discussion. In the course of the work, the reasons for the monetary reform and the reasons for the sharp decline in the country's socio-economic development were revealed. The problems of the country's low level of monetary security are discussed.Conclusion. Based on the results of the study, we can conclude that the use of the money supply targeting regime is the most effective and will be effective in the future. Modern measures of non-inflationary growth of the money supply are proposed.